Forage production and small ruminant grazing responses in Mediterranean shrublands as influenced by the reduction of shrub cover - Papachristou, T G; Platis, P D; PAPANASTASIS, V P (Agroforestry systems, 1996)
Reduction of shrub cover in Mediterranean shrublands is considered as a method of optimising forage and animal production. In this study, forage production in grazed and protected plots and grazing responses of small ruminants in cleared (25% shrub cover), slashed (34'7o shrub cover) and not treated (control, 55% shrub cover) kermes oak (Quercus coccifera L.) shrublands were compared during the spring seasons of 1992, 1993 and 1994. The alterations in shrub density were done in October 1991 and pastures remained ungrazed until spring of 1992. Clearing and slashing of shrub vegetation resulted in higher amounts of available herbaceous forage and useable browse. At the end of the growing season, averaged across years, herbaceous biomass was generally two to three times higher in the treated shrub- lands than in the control; also, browse biomass was slightly less (1,078 vs 1,533 kg/ha) but easily accessible because of the open structure and the lower height of the sprouting shrubs. There were generally no grazing response differences between the cleared and slashed pastures. However, grazing animals (sheep and goats) had a higher bite rate (bites/rain; P ~< 0.05) in the treated pastures than in the control. Levels of crude protein in the forage selected by animals were higher (P ~< 0.05) in the treated pastures than in the control. Animals in the improved pastures maintained diets that were significantly more digestible (53.5%) than those in the control pasture (48.5'7o). Neutral detergent fibre and lignin contents of animal diets were similar in the improved pastures but lower (P <~ 0.05) than those of the control. It is concluded that removing of woody vegetation in Mediterranean shrublands results in increased forage production (available herbage and useable browse) and improved forage quality and availability for small ruminants.
Keywords: Goats; greece; herbs; improvement; Sheep